Dislocating race & nation : episodes in nineteenth-century American literary nationalism - Levine, Robert S. (Robert Steven), 1953- (University of North Carolina Press, 2008)
American literary nationalism is traditionally understood as a cohesive literary tradition developed in the newly independent United States that emphasized the unique features of America and consciously differentiated American literature from British literature. Robert S. Levine challenges this assessment by exploring the conflicted, multiracial, and contingent dimensions present in the works of late eighteenth- and nineteenth-century American and African American writers. Conflict and uncertainty, not consensus, Levine argues, helped define American literary nationalism during this period.